Re‐playing Maimonides' codes: Designing games to teach religious legal systems. - Gottlieb, Owen (Teaching Theology & Religion, 2018)
Lost & Found is a game series, created at the Initiative for Religion, Culture, and Policy at the Rochester Institute of Technology MAGIC Center. The series teaches medieval religious legal systems. This article uses the first two games of the series as a case study to explore a particular set of processes to conceive, design, and develop games for learning. It includes the background leading to the author's work in games and teaching religion, and the specific context for the Lost & Found series. It discusses the rationale behind working to teach religious legal systems more broadly, then discuss the hermeneutics influencing the approach to understanding the legal systems being modeled, and closes with a discussion of the kind of teaching and learning involved in the design of the games and early stage data on the public play of the games.